A PREPARATION, CHARACTERIZATION, AND IN VITRO SKIN PENETRATION OF MORUS ALBA ROOT EXTRACT NANOEMULSION - MAZAYA FADHILA; ABDUL MUN IM; MAHDI JUFRI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: White mulberry (Morus alba) root extract has terpenoid, flavonoid, and stilbene compounds. The stilbenes, oxyresveratrol and resveratrol, have antioxidant and antityrosinase activities. Nanocarriers can help active ingredients to be delivered in a more efficient manner. The advantages of nanoemulsion on products include increased penetration, biocompatibility, and low toxicity due to its non-ionic properties and have the ability to combine the properties of lipophilic and hydrophilic active ingredients. The objective of this study was to prepare, characterize, and evaluate the in vitro skin penetration of M. alba root extract nanoemulsion. Methods: The M. alba root extract was prepared by ionic liquid-based microwave-assisted extraction method. Nanoemulsion was optimized and prepared using virgin coconut oil (VCO), Tween 80, and polyethylene glycol 400 (PEG 400) by aqueous phase-titration method to construct pseudoternary phase diagram. M. alba root extract nanoemulsion was characterized for droplet size, viscosity, zeta potential, and physical stability tests for 12 weeks. In vitro skin penetration of oxyresveratrol from nanoemulsion was determined by the Franz diffusion cell and was compared by macroemulsion preparation, then analyzed by high-performance liquid chromatography method. Results: Based on pseudoternary phase diagram, nanoemulsion of white mulberry root extract contained of 2% VCO and 18% mixture of surfactant Tween 80 and PEG 400 (1:1) was chosen. Nanoemulsion has average globule size of 81.61 nm, with polydispersity index 0.22, and potential zeta −1.56 mV. The cumulative penetration of oxyresveratrol from nanoemulsion was 55.86 μg/cm2 with flux of 6.53 μg/cm2/h, while regular emulsion was 32.45 μg/cm2 with flux of 3.5501 μg/cm2/h. Conclusion: Nanoemulsion of white mulberry root extract was penetrated deeper than regular emulsion.